2015
DOI: 10.1021/acs.est.5b00127
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of Exhaust Emissions from Selected Canadian Marine Vessels: The Case of Trace Metals and Lanthanoids

Abstract: This paper reports the chemical composition of exhaust emissions from the main engines of five ocean going cargo vessels, as they traveled in Canadian waters. The emission factors (EFs) of PM2.5 and SO2 for vessels tested on various intermediate fuel oils (IFO), ranged from 0.4 to 2.2 g kW(-1) hr(-1) and 4.7 to 10.3 g kW(-1) hr(-1), respectively, and were mainly dependent on the content of sulfur in the fuel. Average NOx, CO, and CO2 EFs for these tests were 12.7, 0.45, and 618 g kW(-1) hr(-1), respectively an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 32 publications
(89 reference statements)
6
59
1
Order By: Relevance
“…Another crucial piece of evidence is the elemental analysis of three diesel samples collected during field measurements (shown in Table 4). Vanadium was not detected in any of the three diesel samples, which was significantly different from the data from previous studies (38.0-133.8 mg kg −1 ; Celo et al, 2015) using intermediate fuel oils (IFO) ( Table 4). Regarding vanadium "sources", it can be inferred that if the content of vanadium in fuel keeps declining, the role it plays as a tracer will not be as significant as it has been; furthermore, it will be much harder to detect the existence of vanadium in ambient atmosphere.…”
Section: Comparison Of Vanadium Intensity Between Shipping Emissions contrasting
confidence: 99%
See 3 more Smart Citations
“…Another crucial piece of evidence is the elemental analysis of three diesel samples collected during field measurements (shown in Table 4). Vanadium was not detected in any of the three diesel samples, which was significantly different from the data from previous studies (38.0-133.8 mg kg −1 ; Celo et al, 2015) using intermediate fuel oils (IFO) ( Table 4). Regarding vanadium "sources", it can be inferred that if the content of vanadium in fuel keeps declining, the role it plays as a tracer will not be as significant as it has been; furthermore, it will be much harder to detect the existence of vanadium in ambient atmosphere.…”
Section: Comparison Of Vanadium Intensity Between Shipping Emissions contrasting
confidence: 99%
“…According to Sippula et al's (2014) research on marine diesel engines, Na can also exist in lubrication oil and be exhausted along with the lubrication and grinding process. It is widely recognized that the metal content existent in exhausted particles has a strong correlation with that in fuel (Celo et al, 2015;Moldanová et al, 2013). Although the content of Na is obviously lower than that of vanadium (55-133.8 mg kg −1 ), the peaks of Na + in ion mass spectra are mostly higher than the peaks of the V + / VO + signal.…”
Section: Manual Grouping Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). Gathering evidence revealed that the ratio of V / Ni can serve as a robust indicator of shipping emissions (Tao et al, 2013;Celo et al, 2015;Liu et al, 2017;Viana et al, 2009). A recent study in Shanghai port suggested that the ratio of V / Ni in aerosols emitted from heavy oil combustion of ocean-going ship engines was 3.4 on average (Zhao et al, 2013).…”
Section: Shippingmentioning
confidence: 99%